« Raconter plusieurs histoires à la fois » : Deleuze, de l’empirisme transcendantal au roman moderne - Antoine Brisac (Methodos)
Can transcendental empiricism be the mainstay to devise a poetics of the modern novel? Deleuze synthesizes it into a formula borrowed from Butor: “telling multiple stories simultaneously”. This process, closely related to experimentation in the plastic arts, is based on a new transcendental imagination, which finds what concerns it specifically in the notion of disparation, drawn from Simondon. Cosmos is its emblematic novel. The construction of the Platonic simulacrum already embedded such disparity. But instead of showing several perspectives, the literary simulacrum narrates them, in the form of series, following the structuralist model. They coexist without any of them being privileged, but are nonetheless perspectives on absolutely divergent worlds. In contrast to Finnegans Wake, a simulacrum that complicates all the stories of the world, Borges' Fictions rely on chance so that one and the same story can tell an infinity of outcomes.